2022
DOI: 10.1002/slct.202200527
|View full text |Cite
|
Sign up to set email alerts
|

Band‐Gap Tuned Dilithium Terephthalate from Environmentally Hazardous Material for Sustainable Lithium Storage Systems with DFT Modelling

Abstract: In the fast-developing world, people must migrate to hybrid electric vehicles with a high energy density of lithium-ion batteries to reduce air and sound pollution primarily. Herein, acid hydrolysis is used to depolymerize vest post-consumer polyethylene terephthalate (PET) bottles, resulting in pure terephthalic acid (TPA). It was used in an acid-base reaction to produce the dilithium terephthalate (Li 2 TP). By using 1 H, 13 CNMR, and FTIR spectroscopy, the obtained TPA and its salt Li 2 TP are thoroughly st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…The result reveals that the reversible capacity is due to the presence of the TPA molecule in the Ce‐MOF structure. Thermally less stable (460 °C) [26] organic moiety is eliminated during the process in CeO 2 , and thermally stable up to 550 °C, [37] tannic acid is used for the fabrication of C@CeO 2 by calcination. Among these, C@CeO 2 electrodes gave better responses in electrochemistry due to the morphology‘s micro‐size and a thin layer of carbon coating.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The result reveals that the reversible capacity is due to the presence of the TPA molecule in the Ce‐MOF structure. Thermally less stable (460 °C) [26] organic moiety is eliminated during the process in CeO 2 , and thermally stable up to 550 °C, [37] tannic acid is used for the fabrication of C@CeO 2 by calcination. Among these, C@CeO 2 electrodes gave better responses in electrochemistry due to the morphology‘s micro‐size and a thin layer of carbon coating.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the precipitate is dried in a vacuum oven overnight at 110 °C and used as an organic linker. Also, the pristine TPA has been fabricated as an organic anode for lithium‐ion batteries in previous work [25,26] . Herein, Ce‐MOF is obtained by mixing an equimolar quantity of TPA (recycled from PET) solution with a saturated 1 mmol cerium chloride solution in DMF solvent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the theoretical specific capacity of LiTPA could reach a high value of 290 mAh g –1 . In the past decade, further improvement of the LiTPA-based electrodes has been performed by several research groups and significant progress has been achieved, especially in accelerating the electronic transport in the LiTPA-based electrodes. For instance, Li et al observed that the electronic conductivity of LiTPA could be remarkably enhanced by adding graphene and in situ generated conductive metallic particles. , …”
Section: Introductionmentioning
confidence: 99%